Effect of nanofluids on heat transfer and cooling system of the photovoltaic/thermal performance - Nasrin, Rehena; Hasanuzzaman, Md.; Rahim, Nasrudin Abd (Emerald, 2019)
Purpose: Effective cooling is one of the challenges for photovoltaic thermal (PVT) systems to maintain the PV operating temperature. One of the best ways to enhance rate of heat transfer of the PVT system is using advanced working fluids such as nanofluids. The purpose of this research is to develop a numerical model for designing different form of thermal collector systems with different materials. It is concluded that PVT system operated by nanofluid is more effective than water-based PVT system. Design/methodology/approach: In this research, a three-dimensional numerical model of PVT with new baffle-based thermal collector system has been developed and solved using finite element method-based COMSOL Multyphysics software. Water-based different nanofluids (Ag, Cu, Al, etc.), various solid volume fractions up to 3 per cent and variation of inlet temperature (20-40Â°C) have been applied to obtain high thermal efficiency of this system. Findings: The numerical results show that increasing solid volume fraction increases the thermal performance of PVT system operated by nanofluids, and optimum solid concentration is 2 per cent. The thermal efficiency is enhanced approximately by 7.49, 7.08 and 4.97 per cent for PVT system operated by water/Ag, water/Cu and water/Al nanofluids, respectively, compared to water. The extracted thermal energy from the PVT system decreases by 53.13, 52.69, 42.37 and 38.99 W for water, water/Al, water/Cu and water/Ag nanofluids, respectively, due to each 1°C increase in inlet temperature. The heat transfer rate from heat exchanger to cooling fluid enhances by about 18.43, 27.45 and 31.37 per cent for the PVT system operated by water/Al, water/Cu, water/Ag, respectively, compared to water. Originality/value: This study is original and is not being considered for publication elsewhere. This is also not currently under review with any other journal. © 2019, Emerald Publishing Limited.